2019
DOI: 10.1186/s12879-019-3675-2
|View full text |Cite
|
Sign up to set email alerts
|

A case report of an atypical presentation of pyogenic iliopsoas abscess

Abstract: BackgroundIliopsoas abscess is a collection of pus in the iliopsoas muscle compartment. It can be primary or secondary in origin. Primary iliopsoas abscess occurs as a result of hematogenous or lymphatic seeding from a distant site. This is commonly associated with a chronic immunocompromised state and tends to occur in children and young adults. Secondary iliopsoas abscess occurs as a result of the direct spread of infection to the psoas muscle from an adjacent structure, and this may be associated with traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…Although fever, flank pain, and limited hip movement are the classic triad of psoas abscess, initial symptoms may vary, as does the time required to develop the full triad of symptoms [16, 17]. In our patient, 9 days were required from initial exercise to a correct diagnosis of iliacus muscle abscess.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…Although fever, flank pain, and limited hip movement are the classic triad of psoas abscess, initial symptoms may vary, as does the time required to develop the full triad of symptoms [16, 17]. In our patient, 9 days were required from initial exercise to a correct diagnosis of iliacus muscle abscess.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…The classical clinical triad consisting of fever, backache and limp is present on only 30% of the patients with iliopsoas abscess. 1,2 In one case report of pyogenic psoas abscess the patient had only non-specific leg pain. 2 Psoas abscess can also occur as an unusual complication, Al Shehri et al for example reported a case of late onset iliopsoas abscess due to stump appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is described as collection of pus in the iliopsoas compartment. 1,2 Bound anteriorly by the transversalis fascia, superiorly by endothoracic fascia and inferiorly by the fascia lata of the thigh, the iliopsoas compartment is an extraretroperitoneal space that runs along the posterior aspect of abdomen and pelvis and extends into the thigh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 There are cases in the literature of IPA presenting as exclusively fever and thigh pain. 1,7 If there is suspicion for an IPA, serum laboratory studies such as an elevated white blood cell count, ESR, or CRP, are non-specific, and diagnosis requires imaging. IPAs may be identified on ultrasound, CT, or MRI.…”
Section: Discussionmentioning
confidence: 99%